Avaliação de bioaditivos antioxidantes sobre a estabilidade oxidativa do óleo de linhaça (Linum usitatissimum l.) encapsulado - Nascimento, Malanna Kauanne Gomes do (2017)
Linseed oil is a nutritional oil that has in its constitution unsaturated fatty acids, especially alpha-linolenic. Due to the unsaturations present in the carbonic chain of its fatty acids, this oil becomes the target of oxidizing agents, such as free radicals that act in the triggering of oxidative processes. Consequently, there is a need to protect this oleaginous matrix against the effects of oxidative degradation. Then, some methods be used to protect it like antioxidant bio-additive, encapsulation thecnics or the combined use of these. The objective of this work was to develop linseed oil particles (Linum usitatissimum L.), produced using ionic gelation technology, using cat's claw (Uncaria tomentosa) and barbatimão (Stryphnodendron adstringens) extracts as natural antioxidants. The antioxidant potential of the bioactives was evaluated by controlling the oxidative stability of the flaxseed oil by Rancimat method. The extracts evaluated presented as potential sources of antioxidants by the analyzed results of total phenolic compounds. In the evaluation of the extracts by the DPPH (free radical sequestration) and FRAP (iron reduction) methods, the antioxidant action was confirmed, being superior the cat's nail extract by the two mechanisms studied. The phenolic profile determined by high performance liquid chromatography identified 12 phenolic compounds in the cat nail extract and 9 phenolic compounds in the barbatimão extract. The characterization of the oil obtained from flax seeds indicated a good state of conservation and confirmed a high degree of unsaturation. The presence of a-linolenic acid indicate that the oil is an important source of fatty acids, consequently presenting low oxidative stability. From the ionic gelation encapsulation technology it was possible to obtain a particle of linseed oil with industrial interest concentration. Plus it, high encapsulation efficiency and good oxidative stability together with the use of natural antioxidants obtained from barbatimão extracts and cat's claw. The oxidative stability curves obtained by Rancimat showed that linseed oil particles expressed greater resistance to oxidation than the fluid oils. And the particles containing the cat's claw antioxidant extract showed the greatest protective effect, demonstrating that the encapsulation is A promising alternative to retard the oxidation of oleaginous, combined with the use of antioxidants bio-additives. The increase in the protective effect of the natural antioxidants and the encapsulation technology were confirmed by the accelerated analysis by Rancimat test, justify the transformation of the liquid oil into particulate oil, as it assists in the oxidative stability, allowing its application.